Carbon dioxide sealing-based inhibition of coal spontaneous combustion: A temperature-sensitive micro-encapsulated fire-retardant foamed gel. (15th April 2020) - Xue, Di; Hu, Xiangming; Cheng, Weimin; Wu, Mingyue; Shao, Zhiang; Li, Yongsheng; Zhao, Yanyun; Zhang, Kun
Graphical abstract: Highlights: Temperature-sensitive micro-capsulated inhibitor with paraffin and tea polyphenols. Used CO2 as gas source for foaming and coagulation of gelation system instead of N2. CDSFG-TSRM displayed inhibition effect, cooling, accumulation and gelation. Mechanism of gelation and fire-retardancy of CDSFG-TSRM were investigated. Abstract: In order to enhance the inhibition efficiency of inhibitor on spontaneous combustion of coal and optimize the grouting process of traditional foamed gel, a temperature-sensitive retardant microcapsule (TSRM) was prepared via encapsulation of polyphenols with paraffin. Using composite surfactant (CFA) as a foaming agent and Carbon dioxide (instead of the traditional N2 ) as the gas source, a small amount of TSRM was incorporated into the water glass solution as base material to prepare microcapsuled retardant foamed gel (CDSFG-TSRM). TSRM temperature sensitivity allows melting at 60 °C followed by the release of tea polyphenols, which extends the effective period of tea polyphenols and improves the inhibitory effect on spontaneous coal combustion. Due to the inorganic polycondensation reaction between carbon dioxide and water glass solution, the preparation process of the material reduces carbon dioxide emission as a greenhouse gas and achieves a rapid gelation process of the mixed solution without the addition of a crosslinking agent, hence simplifying the preparation process of foam gel. The combination of in-situ FTIR and TG-IR indicated that the extent of oxidation on the surface hydroxyls of the coal sample treated with CDSFG-TSRM was low and the concentration of ether bond was high. The characteristic absorption peak intensity of C–H structure and Carbon dioxide were obviously weakened, and the characteristic absorption peak of Carbon dioxide appears at a higher temperature. In addition, CDSFG-TSRM has the advantages of shorter extinguishing time, higher retardant efficiency and difficulty in re-ignition.